Freestanding midwife-led units: A narrative review - Grazyna Baczek; Urszula Tataj-Puzyna; Dorota Sys; Barbara Baranowska (Wolters Kluwer Medknow Publications, 2020)
Background: Strengthening of midwives' position and support for freestanding birth centers, frequently referred to as Freestanding Midwife-led Units (FMUs), raise hopes for a return to humanized labor. Our study aimed to review published evidence regarding FMUs to systematize the knowledge of their functioning and to identify potential gaps in this matter. Materials and Methods: A structured integrative review of theoretical papers and empirical studies was conducted. The literature search included MEDLINE, Cochrane, Scopus, and Embase databases. The analysis included papers published in 1977-2017. Relevant documents were identified using various combinations of search terms and standard Boolean operators. The search included titles, abstracts, and keywords. Additional records were found through a manual search of reference lists from extracted papers. Results: Overall, 56 out of 107 originally found articles were identified as eligible for the review. Based on the critical analysis of published data, six groups of research problems were identified and discussed, namely, 1) specifics of FMUs, 2) costs of perinatal care at FMUs, 3) FMUs as a place for midwife education, 4) FMUs from midwives' perspective, 5) perinatal, maternal, and neonatal outcomes, and 6) FMUs from the perspective of a pregnant woman. Conclusions: FMUs offers a home-like environment and complex midwifery support for women with uncomplicated pregnancies. Although emergency equipment is available as needed, FMU birth is considered a natural spontaneous process. Midwives' supervision over low-risk labors may provide many benefits, primarily related to lower medicalization and fewer medical interventions than in a hospital setting.